Whiplash and other useful illnesses - Malleson, Andrew (CEL - Canadian Publishers Collection., 2002)
Whiplash, first described in a medical journal in 1953, now occurs so frequently that in the U.S. alone its annual cost is estimated at between $13 and $18 billion dollars. In Whiplash and Other Useful Illnesses Andrew Malleson contends that whiplash is nothing more than a strain of the neck and, like most other strains, heals in a matter of days or weeks. The fact that up to 10% of all whiplash "victims" are reported as permanently disabled occurs because medical healthcare and legal professionals foster and create illnesses, dangling illusive fortunes in front of would-be claimants. Malleson details the evolution of whiplash from a common, short-lived disorder into a world-wide epidemic that has left millions permanently disabled. He exposes how some medical healthcare and legal professionals prey on the anxieties and greed of their clients. He argues that whiplash is only one of a long list of largely fabricated illnesses and injuries that will drain resources from the health care system.